Diálogos entre nacionalização musical e patrimônio artístico em Mário de Andrade - Moya, Fernanda Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Neste artigo, trarei a tona uma das discussões presentes na minha dissertação de mestrado A Discoteca Pública Municipal de São Paulo: um projeto modernista para a música nacional. Mário de Andrade, ao pensar a criação de uma música nacional – unindo o folclore com o erudito –organizou uma Discoteca Municipal e a colocou como receptora das manifestações artísticas folclóricas recolhidas no Norte e Nordeste do Brasil, em 1938, com o financiamento do Departamento de Cultura de São Paulo, órgão que Mário dirigia. Esta iniciativa, além de endossar a sua nacionalização musical, fundamentava a idéia de transformar a cultura popular em patrimônio, vontade que expressou, em 1936, no anteprojeto não aprovado de criação do Serviço do Patrimônio Artístico Nacional (SPAN) hoje Instituto do Patrimônio Histórico e Artístico Nacional (IPHAN).

In this article I will focus on one of the discussions present in my dissertation Sao Paulo City Public Music Record Collection: a modernist project for Brazilian music. Mario de Andrade, when thinking about the creation of Brazilian music – uniting folklore and classical – organized a Public Music Record Collection and set it up as a receptor of all folklore artistic manifestations collected from the North and Northeast of Brazil. It was founded in 1938 by the Department of Culture of Sao Paulo, an organization headed by Mario de Andrade. This initiative, besides endorsing Brazilian music, was the basis for his idea of transforming popular culture into national heritage, a desire he expressed in 1936 with his draft project, which was not approved at that time, to create the National Artistic Heritage Service (SPAN), which today is the National Historic and Artistic Heritage Institute (IPHAN).
Dialogues on the nationalization of musical and artistic Heritage in the Mário de Andrade project
Keywords: Mario de Andrade; music; heritage; Mário de Andrade; música; patrimônio